The X-factors behind Gen Z employee performance: A systematic review - Derby C. Rampen; Anthony S. Pangemanan; Deske W. Mandagi (Institute of Computer Science (IOCS), 2023)
As significant numbers of Gen Z entering and becoming the majority of the workforce, understanding their unique characteristics, preferences, and motivations is crucial for organizations to effectively manage and engage this generations. This qualitative article delves into the factors affecting Generation Z (Gen Z) employees' performance at work. Despite the existence of well-established research in factors influencing employee performance, there is a notable dearth of a comprehensive review that explores this topic particularly within the context of Gen Z employees. To bridge this theoretical gap, a systematic literature review was undertaken, meticulously gathering pertinent data from scientific articles spanning the period between 2013 and 2022. Utilizing keywords such as motivation, work motivation, job satisfaction, work environment, employee performance, and generation-z, a sistematic process was employed to identify and collect scholarly literature. Following a thorough selection and screening procedure, a refined set of 20 journal articles was meticulously included in the review. The discerned findings underscore the utmost significance of job satisfaction, motivation, leadership team and organizational culture as critical determinants of the performance levels exhibited by Z-generation employees